Free radical-decellularized tissue promotes enhanced antioxidant and anti-inflammatory macrophage response. (November 2019) - LoPresti, S.T.; Popovic, B.; Kulkarni, M.; Skillen, C.D.; Brown, B.N.
Abstract: Oxidative stress leads to the progression of many diseases including chronic wounds, atherosclerosis, stroke and cancer. The modification of biomolecules with reactive nitrogen or oxygen species has been shown to trigger oxidative stress pathways that are beneficial for healing. Extracellular matrix scaffolds have been used successfully in reconstructive applications due to the beneficial host response they induce. To tailor extracellular matrix scaffolds to enhance antioxidant response, ECM were prepared using reactive nitrogen or oxygen species. These scaffolds were shown to be effectively decellularized and possess oxidative or nitroxidative protein modifications. Macrophage responses in vitro and in an in vivo muscle injury model were shown to have enhanced antioxidant phenotypes without impairment of long-term remodeling. These observations suggest that ECM decellularized with reactive oxygen or nitrogen species could provide better outcomes for the treatment of ischemic diseases.